Relación entre la anemia y rendimiento escolar en los estudiantes del décimo año de la Unidad Educativa Gonzanamá en el cantón Gonzanamá. - Eras Curimilma, Ana Judith (2014)
With the objective of having an evaluation concerning the relationship between Anemia and academic performance in students of the 10th grade from the Educational Gonzanamá Unit, in the district of Gonzanamá from the Loja province, a quantitative-analytical and cross-sectional study was performed by evaluating 52 teenagers from this Educational Unit. For this purpose a Microsoft Excel 2010 sheet was created, to facilitate the tabulation of the data. Permission from relevant authorities and the consent of parents of each student was obtained to conduct the study. The diagnose of Anemia was performed by measuring hemoglobin and hematocrit capillary, taking as reference the World Health Organization (WHO) values. Report Cards of each student was also taken into account, having as reference the Education Ministry parameters which give the grade for each student regarding the 2013 – 2014 period. The results showed up that 31% of all students had anemia, and just the 21% of this group has a regular academic performance. Therefore a relationship between Anemia and academic performance exists. Finally a dissemination of the obtained results with those involved in the study was made by giving a talk to parents and students of the Educational Gonzanamá Unit.